Tolerance Induction in Relation to the Eye - Gery, Igal; Caspi, Rachel R. (Frontiers in Immunology, 2018)
Inflammatory intraocular eye diseases, grouped under the term uveitis are blinding conditions, believed to be mediated by pathogenic autoimmune processes that overcome the protective mechanisms of the immune privilege status of the eye. An animal model for these diseases, named experimental autoimmune uveitis (EAU), is induced by initiation of immunity against ocular-specific antigens, or it develops spontaneously in mice with T-cells that transgenically express TCR specific to the target eye antigen(s). T-Cells specific to ocular antigens are generated in the thymus and their majority are eliminated by exposure to their target antigen expressed in this organ. T-cells that escape this negative selection acquire pathogenicity by their activation with the target antigen. In spontaneous EAU, the microbiota play crucial roles in the acquisition of pathogenicity by providing both antigenic stimulation, by molecules that mimic the target ocular antigen, and an additional stimulation that allows invasion of tissues that harbor the target antigen. The pathogenic process is physiologically inhibited by the peripheral tolerance, composed of antigen-specific T-regulatory (Treg) lymphocytes,. Deleting the Tregs enhances the ocular inflammation, whereas adoptively transferring them suppresses the pathogenic response. Potential usage of Treg cells for suppression of autoimmune diseases in humans is under intensive investigation.